ZONA PERKEMBANGAN PROKSIMAL DAN PENDIDIKAN BERBASIS KONSTRUKTIVISME SOSIAL MENURUT LEV SEMYONOVICH VYGOTSKY - Payong, Marselus Ruben (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
This article is a theoretical study of Vygotsky's idea of zone of proximal development. Its aimed at finding out of its relevance to contemporary educational practices that are increasingly complex. Through the description of the background of the emergence of this idea the author concludes that the idea of zone of proximal development is still relevant in modern education, especially to support the educational practices that are friendly toward student’s individual differences at school. Vygotsky's criticism of the practice of levering in schooling is a warning for teachers and education practicioners to consider learning interventions based on individual students' backgrounds especially their mental development differences so that education can be an effective medium to help children's growth and development optimally.